(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Tulisan ini bertujuan untuk menganalisis aspek perlindungan konsumen dalam praktik jasa titip dalam komunitas lari di Jakarta. Permasalahan terletak pada bagaimana perlindungan hukum bagi konsumen akibat kerugian yang dialami dalam Jastip. Rumusan masalah dalam artikel ini adalah bagaimana kedudukan hukum pengguna Jastip dalam komunitas lari sebagai konsumen menurut UU PK. Artikel ini menerapkan pendekatan secara normatif dengan mengaplikasikan bahan hukum primer seperti UU PK, dan KUHPer, dan jurnal-jurnal untuk mendukung bahan hukum sekunder. Data yang dikumpulkan melalui wawancara melalui kuesioner terhadap anggota lari RWRP. Penelitian ini menyimpulkan bahwa konsumen Jastip memiliki hak untuk menerima ganti rugi dari penyedia Jastip dalam hal terjadi cacat produk yang dibeli dari penyedia Jastip. BPSK hadir untuk memfasilitasi sengketa perlindungan konsumen dan menyelesaikan permasalahan di luar pengadilan. Kata kunci: Perlindungan Konsumen, Jasa Titip, Komunitas Lari, Transaksi Nonformal. Abstract This paper aims to analyze the consumer protection aspects within the practice of personal shopping services (Jastip) in a running community in Jakarta. The core issue lies in the extent of legal protection afforded to consumers who suffer losses as a result of Jastip transactions. The research question addressed in this article is: What is the legal status of Jastip users within the running community as consumers under the Consumer Protection Law (CPL)? This study adopts a normative legal approach, utilizing primary legal materials such as the CPL and the Indonesian Civil Code (KUHPer), alongside secondary legal sources including academic journals. Data was collected through questionnaires and interviews with members of the RWRP running community. The study concludes that consumers utilizing Jastip services are entitled to compensation from the service provider in cases of defective products purchased through the Jastip system. The Consumer Dispute Settlement Agency (BPSK) plays a vital role in facilitating consumer protection disputes and providing alternative dispute resolution outside the court system. Keywords: Consumer Protection, Personal Shopper Service, Running Community, Informal Transactions.